Exploring the challenges, strategies, and support needded by ELEP pre-service teachers in implementing lesson plan: a study of ELEP students at Universitas Negeri Padang - Maharani, Puja; Syafei, An Fauzia Rozani (Journal of English Language Teaching, 2025)
This study aims to explore the challenges faced by pre-service teachers, the strategies they employed to overcome these challenges, and the forms of support they required in implementing lesson plans during their teaching practicum. The participants consisted of 43 pre-service teachers from the English Language Education Program (ELEP) at Universitas Negeri Padang who conducted their practicum from January to June 2025. Using a descriptive qualitative approach, data were collected through open-ended questionnaires validated by the thesis supervisor. The data were analysed using thematic analysis guided by three theoretical frameworks: Lampert (2001) on teaching challenges, Hopkins (2008) on teaching strategies, and Zeichner and Liston (2013) on support needed in teaching practice. The findings revealed that pre-service teachers encountered several major challenges, including difficulties in classroom management and teacher–student interaction, adapting to students’ diverse abilities, time limitations, and unexpected classroom situations. To overcome these challenges, they applied strategies based on Hopkins’s models, such as whole-class teaching, cooperative group work, and inductive teaching. Moreover, they required reflective support, professional guidance, and contextual understanding in line with Zeichner and Liston’s framework. In conclusion, the study highlights that while ELEP students demonstrated adaptability and applied appropriate strategies to address teaching challenges, consistent mentoring, reflective feedback, and contextual understanding are essential to enhance the effectiveness of lesson plan implementation and to strengthen teacher education programs in preparing pre-service teachers for real classroom practice.